\begin{align}
I_1(0,x,n)=\int a^{(0)}(x)e^{-nx}dx & = a(x)\left(\int e^{-nx} dx\right)-a'(x)\left(\iint e^{-nx} d^2x\right)+a''(x)\left(\iiint e^{-nx} d^3x\right)-+a'''(x)\left(\iiiint e^{-nx} d^4x\right)+\cdots +(-1)^{R+1}\int a^{(R+1)}(x)\left(e^{-nx}\right)^{(-(R+2))}dx\\
& =\sum_{k=0}^{R}(-1)^ka^{(k)}(x)\left(e^{-nx}\right)^{(-(k+1))} +(-1)^{R+1}\int a^{(R+1)}(x)\left(-\frac{1}{n}\right)^{R+2}e^{-nx}dx\\
& =\sum_{k=0}^{R}(-1)^ka^{(k)}(x)\left(-\frac{1}{n}\right)^{k+1}e^{-nx} -\int a^{(R+1)}(x)\left(\frac{1}{n^{R+2}}\right)e^{-nx}dx\\